Eleven preludes for solo piano by Edmundo Villani-Côrtes: an analysis to understand the pedagogical potential of these piano works for the development of technicalinterpretive skills (Orfeu, 2020)
Edmundo Villani-Côrtes (1930) is one of today’s most prominent Brazilian composers. This article celebrates his ninetieth birthday through an excerpt from a research conducted 15 years ago. Among his over four hundred works, are the eleven preludes for solo piano composed at different times. The aim of this paper was to analyse the preludes following the ideas of Schmalfeldt (2002) and Kochevitsky (1967), and to identify the pedagogical potential by looking at the technical-interpretive skills to be developed in each one according to Uszler's parameters (1995). In addition, a review of the preludes was carried out with the composer. This research reveals the importance of Villani-Côrtes’ piano preludes as pedagogical material and their place in the Brazilian piano music repertoire.
Keywords: Preludes; Edmundo Villani-Côrtes; Piano Pedagogy; Brazilian Contemporary Music